Experimental investigation on the performance degradations of the GaN class-F power amplifier under humidity conditions. (25th February 2021) - Zhou, Shaohua
Abstract: To investigate the humidity dependency of the specifications for a GaN class-F power amplifier (PA), humidity experiments are conducted in the Vötsch Industrietechnik SC 3 1000 MHG environmental test chamber. The experimental results show that the key specifications of the PA, such as the output power and power-added efficiency, the large-signal gain, and the drain current show degradation as humidity increases. The reason for this degradation may be the reduction of the 2DEG mobility density due to surface degradation at AlGaN recess regions caused by diffusion phenomena of Ga, and Al. The results concluded here would be helpful for the PA designers to understand the humidity effects on the key specifications for the GaN class-F PA comprehensively, so that the designers could consider the effects on the design cycle of the compensation circuits in advance.